Study on Satellite Constellation Spare Strategy Based on Markov Process - LUO Tiansu; ZHAO Lingfeng; FENG Yunwen; XUE Xiaofeng; LU Cheng (Hangkong gongcheng jinzhan, 2022)
In response to the issue of reducing satellite constellation backup costs while meeting constellation availability target,it is the hot issue in current research.In this paper,the impact of different spare strategies on the performance of a low earth orbit(LEO)satellite constellation are studied and the best spare strategy that takes into account both the performance and economic efficiency of the constellation is selected.First and foremost,a constellation availability model with degraded operation is developed.Secondly,the Markov process is used to solve this model.Last but not least,the availability of the constellation with different spare strategies at different constellation levels is calculated based on the operation data of a real LEO satellite constellation.The results show that deploying two backup satellites in each orbit can make the constellation with the lowest spare cost while meeting the availability target.The spare strategy proposed in this paper has a certain reference value for the construction of LEO satellite constellations and can provide guidance for the accurate configuration of spare satellites with reasonable cost reduction.